Polygenic risk scores of fasting insulin and insulin-related traits in a Taiwanese Han population - Wei-De Lin; Wen-Ling Liao; Ting-Yuan Liu; Yu-Chia Chen; Chi-Chou Liao; Fuu-Jen Tsai (Cell & Bioscience)
Abstract Background Insulin regulates blood sugar levels and several physiological processes, but many aspects of the relationship between insulin regulation and genes still require further discussion. Thus, this study aimed to explore the genetic variations associated with changes in fasting insulin level in Taiwanese Han individuals through genome-wide association studies (GWAS) and polygenic risk score (PRS) analysis. Results Through GWAS in the primary group and replication in the Follow-up group, no genome-wide significant loci were identified; however, three genes or SNPs, PIP4K2A, FTO, and rs3846601, approached significance. Among them, PIP4K2A and rs3846601 represent novel prominent fasting insulin susceptibility loci identified in this study. Consistency was noted among the target, validation, and Follow-up groups by PRS analysis. Significant associations were observed between fasting insulin level-derived PRS and type 2 diabetes (T2D) and BMI susceptibility. Strong and positive associations traits were found between various diseases/traits in PheWAS, they were morbid obesity, T2D, polycystic ovaries, chronic nonalcoholic liver disease, and hypertension. Conclusions This study identified fasting insulin-related loci and developed a PRS model, offering insights into genetic regulation and potential early risk assessment for metabolic diseases in Taiwanese Han population.